Advances in improving the performance of cellulase in ionic liquids for lignocellulose biorefinery. (January 2016) - Xu, Jiaxing; Xiong, Peng; He, Bingfang
Highlights: The first overview of advances in improving the performance of cellulase in ILs. Screening natural IL-tolerant cellulases from different microhabitats are described. Physical and chemical methods for stabilizing cellulases in ILs are discussed. Improving IL tolerance of cellulase through enzyme engineering are reviewed. Inactivation mechanisms of cellulase in ILs are addressed. Abstract: Ionic liquids (ILs) have been considered as a class of promising solvents that can dissolve lignocellulosic biomass and then provide enzymatic hydrolyzable holocellulose. However, most of available cellulases are completely or partially inactivated in the presence of even low concentrations of ILs. To more fully exploit the benefits of ILs to lignocellulose biorefinery, it is critical to improve the compatibility between cellulase and ILs. Various attempts have been made to screen natural IL-tolerant cellulases from different microhabitats. Several physical and chemical methods for stabilizing cellulases in ILs were also developed. Moreover, recent advances in protein engineering have greatly facilitated the rational engineering of cellulases by site-directed mutagenesis for the IL stability. This review is aimed to provide the first detailed overview of the current advances in improving the performance of cellulase in non-natural IL environments. New ideas from the most representative progresses and technical challenges will be summarized and discussed.